조현병 환자와 발병하지 않은 일차친족에서 인지조절 결함의 비교 - 윤혜림; 우선진; 이상원; 원승희 (Singyŏng chŏngsin ŭihak, 2017)
Objectives This study aimed to identify the differences in the profiles of cognitive control deficits among schizophrenic patients and endophenotypes. Methods The study examined three groups: remitted patients with schizophrenia (n=54), unaffected first-degree relatives of the probands with schizophrenia (n=36), and a healthy control group (n=51), which were all matched for age, sex, and years of education. The AX version of the continuous performance test was used to examine cognitive control. The error rate, correct response times of each subset (AX, BX, AY, BY), and d’ as an indication of the accuracy sensitivity index were calculated. The psychopathology, intelligence, and psychomotor speed were also assessed. Results Patients with schizophrenia showed significantly poorer error rates and d’ in the AX and BX subsets than the others. They showed more delayed correct response times than the healthy control group in all subsets. The first-degree relatives also showed more delayed correct response times in the BX and AY subsets than the healthy control group, but were similar to the patients. Conclusion These findings suggest that cognitive control is impaired in schizophrenia and endophynotypes possibly share this delayed information processing from the higher loading states of cognitive control. KCI Citation Count: 0